2015
DOI: 10.1016/j.jad.2015.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Training mental health professionals in suicide practice guideline adherence: Cost-effectiveness analysis alongside a randomized controlled trial

Abstract: We presented the first randomized trial (trial registration: The Netherlands Trial Register (NTR3092 www.trialregister.nl)) on cost-effectiveness of a suicide practice guideline implementation in mental health care. The intervention might be considered cost-effective for depressed suicidal patients if society is willing to make substantial investments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Training health professionals may increase the likelihood of guideline adherence, and in a number of studies, have been shown to have had positive suicide preventive effects (for reviews see [ 1 , 2 , 8 ]). This has been shown worldwide for different target groups with a range of different procedures and curriculums aimed at the prevention of suicide, where activities often revolve around increasing awareness and recognition of warning signs of suicide, improving adherence to recommended treatment-practices of associated mental health problems such as depression [ 9 , 10 , 11 ]. It is likely that these types of educational activities, not only increase the level of knowledge among health-care professionals but also improve attitudes (especially when the negative attitudes stem from a lack of knowledge about suicide prevention).…”
Section: Introductionmentioning
confidence: 99%
“…Training health professionals may increase the likelihood of guideline adherence, and in a number of studies, have been shown to have had positive suicide preventive effects (for reviews see [ 1 , 2 , 8 ]). This has been shown worldwide for different target groups with a range of different procedures and curriculums aimed at the prevention of suicide, where activities often revolve around increasing awareness and recognition of warning signs of suicide, improving adherence to recommended treatment-practices of associated mental health problems such as depression [ 9 , 10 , 11 ]. It is likely that these types of educational activities, not only increase the level of knowledge among health-care professionals but also improve attitudes (especially when the negative attitudes stem from a lack of knowledge about suicide prevention).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining study focused on the role of the media (Knapp, McDaid, & Personage, 2011; Law & Yip, 2011; Mihalopoulos et al, 2011; Whitmer & Woods, 2013). Eight studies investigated selected interventions, such as suicide education and support, while five studies looked at indicated interventions, such as the use of videoconference to assess patients in remote areas, a joint crisis plan for adults with borderline personality disorder, provision of emergency contact cards to people who have previously self-harmed, as well as early intervention for people with first-episode psychosis and for adolescents in juvenile court (Borschmann et al, 2013; de Beurs et al, 2015; Doran, Ling, Gullestrup, Swannell, & Milner, 2016; Gray, Dawson, Grey, & McMahon, 2011; Jong, 2004; Knapp et al, 2011; Mihalopoulos et al, 2011; netbalance, 2014; Park, McCrone, & Knapp, 2016; Pil, Pauwels, Muijzers, Portzky, & Annemans, 2013; Sari, de Castro, Newman, & Mills, 2008; van Spijker, Majo, Smit, van Straten, & Kerkhof, 2012). Finally, two studies consisted of several programs that combined universal and selective components, including awareness-raising, responsible media conduct, and outreach programs (Platt et al, 2006; Zaloshnja et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…El financiamiento en capacitaciones en profesionales de la salud se da principalmente en intervenciones relacionadas a desnutrición/anemia en promedio de 4,3 millones de soles (1,3 millones de dólares), así como intervenciones en relación a salud maternoneonatal (planificación familiar, control prenatal y atención del parto) que estimó un promedio de 2,1 millones de soles (654 mil dólares). De acuerdo a los estudios desarrollados por Garcés et al 14 , identifican similares resultados; sin embargo, es muy reducido el financiamiento capacitación en intervenciones de prevención y control del cáncer, enfermedades no transmisibles, TBC-VIH/Sida, Salud Mental siendo intervenciones también relevantes [15][16][17][18] .…”
Section: Discussionunclassified